Sosialisasi Urgensi Pencatatan Perkawinan dan Dampak Perkawinan di Bawah Tangan di Majlis Taklim As-Sakinah Babakancikao Purwakarta - Gussevi, Sofia; Iswanto, Candra; Dzulhijah, Dianra (Yayasan Cendekia Gagayunan Indonesia, 2024)
This service activity is motivated by research results and social phenomena that often occur in society. Many people still carry out private marriages (unregistered marriages). Sometimes they already know the impact, but for certain reasons, they still do it. Even though this legal act violates the positive Islamic law that applies in Indonesia. In Law Number 1 of 1974 (Marriage Law) concerning Marriage, article 2 paragraph (2) states that every marriage is recorded according to the applicable laws and regulations. Similarly, article 5 paragraph (1) of the Compilation of Islamic Law (KHI) states that in order to ensure orderly marriages for the Islamic community, every marriage must be recorded. Marriage registration is regulated because without registration, a marriage has no legal force. Based on this, this activity aims to implement the results of research that has been carried out using the extension method. The results of this activity show that there are still many people who do not heed the positive Islamic law that applies in Indonesia, they think that only Islamic law needs to be applied. There are many illegal marriages which actually violate positive Islamic law in Indonesia because the administrative requirements for marriage are not fulfilled, namely that the marriage must be registered. By holding this service, it is hoped that the public will be able to know and understand the urgency of registring marriages and the impacts caused by illegal marriages.